جوانب من أحداث ماي - جوان 1945 بقالمة من خلال وثائق رسمية فرنسية - بورغدة, رمضان (جامعة الوادي - University of Eloued, 2013)
Abstract: Aspects of the events of May - June 1945 in Guelma through French official documents In this study, I will focus on incidents of May - June 1945 in the area of Guelma, which began on May 08, 1945, with peaceful demonstrations holding r national demands, but the French authorities committed great massacres against these peaceful demonstrators. The gradual allowance of the French authorities to historians to study the French archive of that period made it possible to detect serious aspects of the colonial oppression of the Algerian Muslims. I will confine myself, in this context, to the study and analysis of three issues that I consider very important, namely:. - The European militias and their crimes in Guelma and its nearby areas - The fate of the missing Algerian Muslim - The impact of incidents on European settlers. We will see how the oppression was a kind of genocide and a crime against the humanity ( if we use a modern term) that the French authorities are responsible of and will never lose their validity through history .
مقال
Keywords: 8ماي 1945.قالمة.مجازر.الاستعمار الفرنسي.مظاهرات